?INFLUENCE OF NUTRIENTS ON THE BIOLOGICAL OXIDATIVE ACTIVITIES OF ALOCALLY ISOLATED THIOBACILLUS FERROOXlDAN - Rahman, Mujeeb ur; Gul, Shereen (Biological Sciences - PJSIR, 2001)
The strain of Thiobacillusferrooxidan was isolated from the Sorange coal mine water in ferrous sulphate medium. The effects of inorganic nitrogen (NH4+' NO)-) and phosphate on the biological oxidation of copper sulphide ore were examined. It is observed that the iron was solubilized first from FeS2 or Fet • x S to as Fe'" and then oxidized to Fe"'", The dissolution of iron Fe'" was a chemical reaction whereas the conversion of Fe'" to Fe"'" was bacteria mediated. The addition and increase in the concentration of phosphate delayed and reduced the conversion of Fe'" to Fe"'". Ammonium was found to be the preferred source of nitrogen for the isolated bacterium. The nitrogen as NH/ increased the Fe'" oxidation whereas NO)· had negative effect. The solubilization of copper was directly related to the Fe'" iron oxidation. Maximum dissolved copper concentration were observed in 6mM ammonium supplemented medium and minimum in 6mM nitrate.